Analisis Penerapan Prinsip Operasional Lembaga Keuangan Syari’ah Pada Sistem Keuangan Koperasi Simpan Pinjam Dan Pembiayaan Syari’ah Al-Uswah Indonesia - Nanang Sobarna (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Al Uswah Indonesia Sharia Savings and Loans Cooperative is a cooperative business entity that collects funds from the public and distributes it to members in the form of financing based on sharia principles. This includes the application of operational principles to the financial system of KSPPS Al-Uswah Indonesia must be in accordance with sharia principles in regulating its financial system because the operation of this financial system will affect the financial performance of KSPPS Al-Uswah Indonesia. The purpose of this study is to find out the application of the operational principles of Islamic financial institutions at KSPPS Al Uswah Indonesia. The research method used is the case study method with a descriptive qualitative approach. The application of the operational principles of sharia financial institutions to the financial system of KSPPS Al-Uswah Indonesia has been implemented in accordance with the provisions of sharia principles that exist in sharia financial institutions as sharia cooperatives.